P50 Using simulation to improve medical student confidence in the assessment and management of serious falls. (November 2018) - Tulloch, Laura; McIldowie, Beth; Wells, Helena; Jones, Tiffany; Benbow, Aled; Simonds, Luke
Abstract : Background: With around 2 50 000 inpatient falls reported each year in UK hospitals, each potentially carrying the risk of a patient coming to harm, it is vital that newly qualified doctors are confident in the assessment and management of a fall. 1 2 Junior doctors need to rapidly identify and appropriately manage any injuries whilst considering underlying causes and risk factors for further falls. Serious falls present complex and challenging clinical demands and our students reported a low confidence level in their ability to undertake a role in the patient assessment. Summary of work: We designed and implemented a simulation scenario in which final year medical students are called to assess an elderly patient who has fallen outside the ward. The students are expected to assess the patient and initiate immediate management for their suspected injuries. As the scenario takes place outside of the simulated ward environment the students must also consider the implications of moving, or not moving, the patient, who has sustained significant injuries. Students were provided with their peers as the 'medical emergency team', hence encouraging them all to consider the different roles required in managing this patient. The scenario is followed by a debrief between students and faculty in which the key learning points are discussed with particular focus on the human factors issues that arise. Summary of results: We used a pre- and post-simulation questionnaire to gather feedback from the participants. Following the simulation, we found a significant improvement in reported student confidence levels, an increase from a mean of 2.8 to 4.5 on a six point Likert scale (p<0.01). The students also reported intentions to look further into falls guidelines and felt that having a larger number of participants in the simulation suite highlighted the importance of team work and communication when managing acutely unwell patients. Discussion and conclusions: With junior doctors undertaking a significant role in falls assessment it is important that they are well prepared to do so. Simulating a patient fall, which has occurred away from the patient's bedside, was found to be a useful tool for improving student confidence, encouraging them to consider further study and highlighting the influence of human factors in these difficult scenarios. Recommendations: Going forward, there would be a particular benefit to undertaking this simulation with other multidisciplinary team members, increasing fidelity and enabling further exploration of the influence of human factors in the real clinical environment References: National Patient Safety Agency. Rapid response report: Essential care after an inpatient fall 2011. United Kingdom: NHS. Royal College of Physicians. National audit of inpatient falls: Audit report 2017. London: RCP.